Strategic Planning of Infrastructure Development: BIM and Intelligent Building - BAKHAREVA, Olga (Journal of Advanced Research in Law and Economics, 2019)
Nowadays there is a complex problem of irrational use of natural resources in an old housing stock operation. The purpose of the study is to develop a concept for the development of the old real estate of the historic city center for the ecological and energy efficient use of and preserving the city’s identity. During this research of energy losses, the following methods were used: an institutional research on the basis of an analysis of technical documentation and a defects in the design, construction and operation; an examination of technical documentation and a field research of defects; synthesis of recommendations for householders to control opportunistic behavior of managers in elimination of defects of the building. As a result, the defects of the old building in the historical centre of cities, emerging during the construction and operation phases, were identified and analyzed. The method of moving the building into the category of energy-efficient buildings is based on the energy-saving design, information modelling technology, intelligent technologies. We propose creation of system of regional strategic planning transition from the old housing stock to energy-efficient buildings based on synchronization of innovation and innovation cycles and require intellectual support from the public authorities. It can be considered within the framework of the concept of sustainable urban development. The regional investment program, involving creation and maintenance of energy-efficient real estate can reduce energy consumption and carbon dioxide emissions at all the stages of the building's life.